Model for Wireless Base Station Goodput Evaluation in Vehicular Communication Systems - Ipatovs, A.; Petersons, E.; Jansons, J. (Elektronika ir Elektrotechnika, 2011)
In this paper we present the model of wireless base station goodput evaluation. There was used access point model as queuing system with different kind of requests and cycling auto traffic model. Wireless mobile networks have different parameters, such as client stations distance to access point, number of clients in wireless network range, vehicle speed and traffic type. These parameters were analyzed and presented in this paper. Ill. 5, bibl. 17 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.348